Tax Administration in Developing Countries : An Economic Perspective - Mansfield, Charles (IMF Working Papers; Working Paper ;, 1987)
This paper examines the role of tax administration in developing countries from an economic perspective. The traditional separation of tax policy and tax administration in the literature is shown to break down in developing countries, where tax administrators decide in what manner complicated tax legislation should actually be applied. After surveying economic literature dealing with tax administration, the paper offers guidelines on how tax administrators can help implement more efficient and equitable tax systems.